Pembelajaran Berbasis Proyek Untuk Meningkatkan Pembelajaran Matematika Kelas VI Di Era Digital - Rahmat, Rahmat; Mahmudah, Istiyati (Galois: Jurnal Penelitian Pendidikan Matematika, 2025)
MIN 2 Palangka Raya lerning requires optimization to face challenges in the digital era, tecnologi advances affect educational methods. In this article, we look at how the application of PJBL in mathematics learning at MIN 2 Palangka Raya in the digital era can be optimized and have an impact on student learning outcomes. PJBL is a project-based learning method that emohasizes student participation solving real problems coorperatively. The PJBL method allows students to learn mathematics through real-world experience and theory. During this process students are given the task of applying the mathematical concepts they have learned. Students can more easily understand abstract concepts with digital technology such as interactive learning applications, mathematical simulations and data processing software. It has been proven that optimizing PJBL mathematicas learning increases student involvement in the learning process. Because learning seems more applicable and meaningful, they are more motivated and meaningful, they are more motivated and enthusiastic. In addition, students utilize digital technology to gain access to various sources of inromation, which helps them understand mathematicas betel. With PJBL, students not only improve their understanding of mathematics, but they also gain critical thinking problem solving skills, and the ablitity to work in grousps and independently. They evaluation results show that the use of PJBL in class VI MIN 2 Palangka Raya has succeeded in increasing students’ mathematics achievement. Overall, with the support of digital technology, PJBL has the ablity to optimize mathematics learning, create a dynamic learning environment, and prepare students to face challenges in the digital era.